Analisis Pelaksanaan Pengadaan Barang/Jasa Secara Elektronik pada Pemerintah Kabupaten Gresik - Purnomo Edi Mulyono* (Airlangga Development Journal, 2017)
Benefits of e-procurement is not only for the agency or the developer of the system itself but also for the providers of goods and services and the general public who want to know the process of procurement of goods and services procurement organizers get More bid prices and more simple nobility processes. As for the provider of goods/services can expand the business opportunity, create a healthy business competition, open the opportunity of business actors openly for anyone and reduce administrative costs. Additionally, e-procurement is also believed to improve collaboration between buyers and suppliers, reducing personnel needs, improving coordination, reducing transaction costs, shorter buying and selling of goods, facilitating Greater inventory and transparency. Information technology can make costs more effective and public procurement systems are more innovative.